C3 Glomerulopathy and Related Disorders in Children: Etiology-Phenotype Correlation and Outcomes. Issue 11 (November 2021) - Wong, Edwin K.S.; Marchbank, Kevin J.; Lomax-Browne, Hannah; Pappworth, Isabel Y.; Denton, Harriet; Cooke, Katie; Ward, Sophie; McLoughlin, Amy-Claire; Richardson, Grant; Wilson, Valerie; Harris, Claire L.; Morgan, B. Paul; et al.
Visual Abstract: Abstract : Background and objectives: Membranoproliferative GN and C3 glomerulopathy are rare and overlapping disorders associated with dysregulation of the alternative complement pathway. Specific etiologic data for pediatric membranoproliferative GN/C3 glomerulopathy are lacking, and outcome data are based on retrospective studies without etiologic data. Design, setting, participants, & measurements: A total of 80 prevalent pediatric patients with membranoproliferative GN/C3 glomerulopathy underwent detailed phenotyping and long-term follow-up within the National Registry of Rare Kidney Diseases (RaDaR). Risk factors for kidney survival were determined using a Cox proportional hazards model. Kidney and transplant graft survival was determined using the Kaplan–Meier method. Results: Central histology review determined 39 patients with C3 glomerulopathy, 31 with immune-complex membranoproliferative GN, and ten with immune-complex GN. Patients were aged 2–15 (median, 9; interquartile range, 7–11) years. Median complement C3 and C4 levels were 0.31 g/L and 0.14 g/L, respectively; acquired (anticomplement autoantibodies) or genetic alternative pathway abnormalities were detected in 46% and 9% of patients, respectively, across all groups, including those with immune-complex GN. Median follow-up was 5.18 (interquartile range, 2.13–8.08) years. Eleven patients (14%) progressed to kidney failure, with nine transplants performed in eight patients, two of which failed due to recurrent disease. Presence of >50% crescents on the initial biopsy specimen was the sole variable associated with kidney failure in multivariable analysis (hazard ratio, 6.2; 95% confidence interval, 1.05 to 36.6; P< 0.05). Three distinct C3 glomerulopathy prognostic groups were identified according to presenting eGFR and >50% crescents on the initial biopsy specimen. Conclusions: Crescentic disease was a key risk factor associated with kidney failure in a national cohort of pediatric patients with membranoproliferative GN/C3 glomerulopathy and immune-complex GN. Presenting eGFR and crescentic disease help define prognostic groups in pediatric C3 glomerulopathy. Acquired abnormalities of the alternative pathway were commonly identified but not a risk factor for kidney failure.